INVESTIGATION OF THE EFFECT OF EMPLOYEES' LEARNING ORGANIZATION PERCEPTION ON EMPLOYEE MOTIVATION IN AIRLINE BUSINESSES (Third Sector Social Economic Review, 2022)
The aim of this research is to examine the effect of the learning organization perceptions of the personnel working in the airline companies on their motivation. In this context, the learning organization perception scale was evaluated over seven sub-factors, and the effect of each factor on employee motivation was evaluated. The sample group of the research consists of 459 personnel working in airline companies operating in Istanbul. Although the number of employees is unknown, data were collected using the convenience sampling method. Questionnaire technique was used as the data collection method and the data were collected face to face. SPSS statistical program was used in the analysis of the collected data. Multiple linear regression analysis was used to test the hypotheses. According to the research results, Dialogue and research perception, sharing systems perception, reinforced employee perception and supportive leadership perception affect employee motivation positively. On the other hand, Continuous learning perception, team learning perception and inter-system connection perception do not affect employee motivation in a positive way. It is expected that the findings of the study will shed light on the importance of using learning organizations in the management process in airline companies and on which points they can contribute.
Keywords: Airline Business; Employee motivation; Learning organizations